Epigenome-wide DNA methylation analysis reveals differentially methylation patterns in skeletal muscle between Chinese Chenghua and Qingyu pigs - Kai WANG; Ping-xian WU; Shu-jie WANG; Xiang JI; Dong CHEN; An-an JIANG; Wei-hang XIAO; Yan-zhi JIANG; Li ZHU; Yang-shuang ZENG; Xu XU; Xiao-tian QIU; et al. (Journal of Integrative Agriculture, 2022)
Chenghua (CH) pig and Qingyu (QY) pig are typical Chinese native fatty breeds. CH pig is mainly distributed in Chengdu Plain, while QY pig is widely distributed throughout the mountain areas around the Sichuan Basin. There are significant differences in their phenotypic traits, including body image, growth performance, and meat quality. This study compared several meat quality traits of CH and QY pigs and conducted a genome-wide DNA methylation analysis using reduced representation bisulfite sequencing (RRBS). It was observed that the pH at 45 min (pH45min, P=5.22e–13), lightness at 45 min (L*45min, P=4.85e–5), and lightness at 24 h (L*24h, P=3.57e–5) of CH pigs were higher than those of QY pigs. We detected 10 699 differentially methylated cytosines (DMCs) and 2 760 differentially methylated genes (DMGs) associated with these DMCs. Functional analysis showed that these DMGs were mainly enriched in the AMPK signaling pathway, Type II diabetes mellitus, Insulin signaling pathway, mTOR signaling pathway, and Insulin resistance. Furthermore, 15 DMGs were associated with fat metabolism (ACACA, CAB39, CRADD, CRTC2, FASN, and GCK), muscle development (HK2, IKBKB, MTOR, PIK3CD, PPARGC1A, and RPTOR), or meat quality traits (PCK1, PRKAG2, and SLC2A4). The findings may help to understand further the epigenetic regulation mechanisms of meat quality traits in pigs and provide new basic data for the study of local pigs.